2000
DOI: 10.1093/ajcn/72.6.1503
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the effects of polydextrose intake on physiologic functions in Chinese people

Abstract: Polydextrose ingestion had significant dietary fiber-like effects with no laxative problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
156
5
24

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(198 citation statements)
references
References 24 publications
13
156
5
24
Order By: Relevance
“…In conclusion, this study confirmed several of the findings previously determined in a human clinical study (19). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In conclusion, this study confirmed several of the findings previously determined in a human clinical study (19). …”
Section: Discussionsupporting
confidence: 92%
“…In one study, polydextrose has been shown to express prebiotic effects; it decreased fecal pH, increased the residual concentration of short chain fatty acids (SCFA), and increased numbers of bifidobacteria in feces (19). In the present study we further evaluated the prebiotic potential of polydextrose and lactitol (selective fermentation by gut bacteria) by using an in vitro model of the human colon (25).…”
mentioning
confidence: 99%
“…*X 1 : Powder milk concentration expressed in g&100 g beverage, **X 2 : Ricotta cheese whey concentration expressed in g&100 g beverage It was not possible to verify the influence of different polydextrose concentrations on the count of probiotic microorganisms. However, the use of prebiotics is beneficial to the host, benefits such as decreasing fecal pH, increasing residual concentration of short chain fatty acids and increasing the number of bifidobacteria in feces (Jie et al, 2000). Thus, its use as a raw material is justified.…”
Section: Survival Of Acid Lactic Bacteria During Storage Of Fermentedmentioning
confidence: 99%
“…Além disso, este polímero é extremamente estável, incolor e não apresenta sabor residual, sendo também altamente estável dentro de uma faixa ampla de pH, temperatura, condições de processamento e estocagem (JIE, 2000). É tolerada uma média de 90 g por dia, sem efeitos laxativos (FAKHOUR et al, 2005).…”
Section: Introductionunclassified
“…É tolerada uma média de 90 g por dia, sem efeitos laxativos (FAKHOUR et al, 2005). Segundo Jie et al (2000), a polidextrose pode ser também considerada como pré-biótico, pois estimula o crescimento de lactobacilos e bifidobactérias e a fermentação contínua ao longo do cólon. Esta última promove a redução do pH fecal e a produção de ácidos graxos de cadeia curta, destacando-se o butirato, que pode reduzir riscos de câncer.…”
Section: Introductionunclassified